SEMIGROUPS OF LINKED UPFAMILIES - Гаврилків, Володимир Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Given a semigroup S we study right and left zeros, idempotents, the minimal ideal, left cancelable and right cancelable elements of the semigroup N (S ) of linked upfamilies and characterize groups G whose extensions N (G ) are commutative.